The lived experience of chronic headache: a systematic review and synthesis of the qualitative literature - Nichols, VP; Ellard, DR; Griffiths, FE; Kamal, A; Underwood, M; Taylor, SJC (BMJ, 2017)
Objective To systematically review the qualitative literature of the lived experience of people with a chronic headache disorder. Background Chronic headaches affect 3%–4% of the population. The most common chronic headache disorders are chronic migraine, chronic tension-type headache and medication overuse headache. We present a systematic review and meta-ethnographic synthesis of the lived experience of people with chronic headache. Methods We searched seven electronic databases, hand-searched nine journals and used a modified Critical Appraisal Skills Programme checklist to appraise study quality. Following thematic analysis we synthesised the data using a meta-ethnographic approach. Results We identified 3586 unique citations; full texts were examined for 86 studies and 4 were included in the review. Included studies differed in their foci: exploring, patient-centred outcomes, chronic headache as a socially invisible disease, psychological processes mediating impaired quality of life, and the process of medication overuse. Initial thematic analysis and subsequent synthesis gave three overarching themes: ‘headache as a driver of behaviour’ (directly and indirectly), ‘the spectre of headache’ and ‘strained relationships’. Conclusion This meta-synthesis of published qualitative evidence demonstrates that chronic headaches have a profound effect on people’s lives, showing similarities with other pain conditions. There were insufficient data to explore the similarities and differences between different chronic headache disorders.